Prediction of swimming performance times using a mixed model of physiological and stroke variables - Nagle, E. F.; Robertson, R. J.; Zoeller, R. F.; Moyna, N. M.; Goss, F. L. (Medicine & Science in Sports & Exercise, 1998)
Physiological and stroke dynamic testing does not yield great amounts of insight into either 50 or 500-yard performances. Distance per stroke and velocity of swimming at VO2max appear to be the only variables worthy of consideration among those used in this investigation.